Vibronic coherence contributes to photocurrent generation in organic semiconductor heterojunction diodes - Qingzhen Bian (Nature Portfolio, 2020)
Although coherent vibrational motion in donor-acceptor blends may contribute to photogeneration generation in organic solar cells (OSCs), proof of a direct correlation is still lacking. Here, the authors report the role of vibrational coherence on photocurrent generation in ternary OSC blends.